The Benefit of Interferon-Gamma Release Assay for Diagnosis of Extrapulmonary Tuberculosis - Cleopas Martin Rumende; Edward J Hadi; Gloria Tanjung; Imelda N Saputri; Raditya Sasongko (Interna Publishing, 2018)
Background: there are many researches about IGRA in extrapulmonary Tuberculosis (TB), but there only few data from developing countries. This was the first research about the utility of IGRA in extrapulmonary TB performed in Indonesia as developing country with the 2nd most frequent of TB cases in the world. This study aimed to identify the advantage of IGRA examination in diagnosing extrapulmonary TB. Methods: eighty-four patients, presumed to have extrapulmonary TB were examined with IGRA and gold standard examination. The gold standard examination was performed by histopathologic examination, and tissue smear for acid-fast bacilli. Results: among 84 patients included in the study, 57 patients were tested positive with gold standard, where 50 patients among them were also tested positive with IGRA. Among 27 patients tested negative with gold standard, IGRA positive was found in 10 patients. Lymphadenitis was the most common manifestation of the extrapulmonary TB. Diagnostic test from IGRA for extrapulmonary TB found as follows: sensitivity 87,71%, specificity 63%, positive predictive value 83,33%, and negative predictive value 70,83%. Conclusion: IGRA could be used as supporting tool in the diagnosis of extrapulmonary TB. The negative result, however, does not indicate absence of TB infection.